Application of Geographic Information Systems in agriculture: A case study on Development of a forecast model for strategic control of ruminant liver fluke disease in Ethiopia - Jobre, Y. (Ethiopian Agricultural Research Organization, 2003)
This study is conducted to develop a GIS forecast and risk assessment model for fasciolosis in Ethiopia based on physical environmental determinants including moisture and thermal regimes; and to validate the model by comparing risk indices and environmental determinants to available survey data. The paper ends with recommendations including chemotherapy. And it outlines future studies.